2014
DOI: 10.3109/10717544.2013.873501
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-loaded mixed micelles: preparation, optimization, physicochemical properties and cytotoxicityin vitro

Abstract: Although curcumin (CUR) can inhibit proliferation and induce apoptosis of tumors, the poor water solubility restricted its clinical application. The aim of this study was to improve the aqueous solubility of CUR and make more favorable changes to bioactivity by preparing curcumin-loaded phospholipid-sodium deoxycholate-mixed micelles (CUR-PC-SDC-MMs). CUR-PC-SDC-MMs were prepared by the thin-film dispersion method. Based on the results of single factor exploration, the preparation technology was optimized usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 34 publications
3
34
0
Order By: Relevance
“…In previous studies, various drug delivery systems, including lecithin complexes and nanoparticles, have been developed to overcome the aforementioned limitations of baohuoside I (Jin et al, 2012a,b). Among the several micellar formulations evaluated as carriers of anticancer drugs, mixed micelles are the appropriate choice for the carriers of baohuoside I. Micellar systems have many advantages such as increasing the drug solubility, circumventing the uptake by the reticuloendothelial system (RES), improving circulation time, and passive tumor targeting by the enhanced permeability and retention (EPR) effect (Fang et al, 2011;Duan et al, 2015). In addition, mixed micelles have synergistic properties such as increased drug stability and drug loading efficiency compared with that of the individual components (Potluri & Betageri, 2006;Chen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, various drug delivery systems, including lecithin complexes and nanoparticles, have been developed to overcome the aforementioned limitations of baohuoside I (Jin et al, 2012a,b). Among the several micellar formulations evaluated as carriers of anticancer drugs, mixed micelles are the appropriate choice for the carriers of baohuoside I. Micellar systems have many advantages such as increasing the drug solubility, circumventing the uptake by the reticuloendothelial system (RES), improving circulation time, and passive tumor targeting by the enhanced permeability and retention (EPR) effect (Fang et al, 2011;Duan et al, 2015). In addition, mixed micelles have synergistic properties such as increased drug stability and drug loading efficiency compared with that of the individual components (Potluri & Betageri, 2006;Chen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The common advantage of these drug delivery systems is that micelles are resistant to glomerular filtration, which could extend their retention time in the blood. 18 Furthermore, micelles can facilitate the passage of drugs through the blood-brain barrier and blood-spinal cord barrier (BSCB), increasing therapeutic efficacy and safety compared to conventional pharmaceutical dosage forms. 19 There have been several reports of biodegradable polymeric micelles for SCI treatment.…”
mentioning
confidence: 99%
“…These data illustrated that the loading of drugs did not increase the size significantly. It has been reported that the nanoparticles with the size less than 200 nm can significantly accumulate in tumor by ''filtration'' mechanism (Xu et al, 2009;Duan et al, 2015). Small particles are also minimal endocytosis by macrophages, so destruction and clearance could be minimized, and the nanocarriers were desirable for in vitro and in vivo drug delivery (Accardo et al, 2012;Wang et al, 2013).…”
Section: Nlcs Characterizationmentioning
confidence: 99%